Association between mood states and performance of Brazilian elite sailors: Winners vs. non-winners Asociación entre estado de ánimo y el rendimiento de regatistas brasileños de élite: Ganadores vs. no ganadores - Brandt R. (2016)
© 2016, Universidad Catolica San Antonio Murcia. All rights reserved.Sailing is a sport that requires optimum emotional balance for athletes to be able to yield optimum performances, given its unique peculiarities, where six mood states are identified as decisive, such as, high level of vigor and lower levels of tension, depression, anger, fatigue and mental confusion. The purpose of this study is to assess the association between mood states and athletic performance of sailors in different high performance competitions. Sixty-two elite sailors of single-handed and group classes participated in four major competitions. Assessment was carried out at the competition venues and the mood state was assessed using the Brunel Mood Scale. First-place winners in the four competitions showed different mood states from those who finished the races in other positions, especially taking into account depression (p < 0.01), vigor (p < 0.001) and fatigue (p < 0.001). Sailors with lower depression (OR = 0.70) and fatigue levels (OR = 0.80), and greater vigor levels (OR = 1.26) proved to be more likely to win the race. The results corroborate the available scientific data focusing on the relationship between mood states and athletic performance.